Is Delayed Mental Health Treatment Detrimental to Employment? - Prudon, Roger (The Review of Economics and Statistics, 2025)
Abstract Waiting times for mental health treatment have been increasing in many countries. Using administrative data on all inhabitants of the Netherlands and exploiting exogenous variation at the municipality level, I find that these waiting times have substantial repercussions on labor market outcomes for at least eight years after the start of treatment. A one-month (0.5 SD) increase in waiting time decreases the probability of employment by two percentage points. Vulnerable groups with lower educational attainment or a migration background are especially affected given that the impact of waiting time is larger for them and their average waiting time is longer.